PTU-026 Cytological yield of biliary brushings obtained during endoscopic retrograde cholangio pancreatography (ercp): a single centre experience. (22nd June 2015) - Sugumaran, A; Thompson, I; Yeoman, A; Allison, M; Czajkowski, M
Abstract : Introduction: British Society of Gastroenterology (BSG) guidelines recommend cytological analysis of brushings taken from biliary strictures to support diagnosis of malignancy in suspected individuals. There is wide variation reported in literature on test sensitivities ranging between 16% and 65%. We set out to report a single centre experience on the diagnostic yield of cytology specimens of biliary strictures obtained from ERCP. Method: Retrospective analysis on all biliary brushings taken between 2008 and 2011 was performed. All ERCPs were performed by two experienced endoscopists. Routinely, the cytology brush is sent to the lab immediately after the procedure, analysis undertaken by liquid-based methodology and results verified by a histopathologist with special interest in pancreato-biliary disorders. The brushing result was then correlated with the final diagnosis ('suspicious' and 'atypical cells' in cytology report were considered malignant for audit purposes). Results: Cytological specimens taken from 89 patients supported diagnosis of benign or malignant pathology in 67 showing an overall sensitivity of 75.3%. The sensitivity correlating with detection of any malignancy was 71%; It was higher in cholangiocarcinoma (77.8%) compared to detection of pancreatic carcinoma (71%). The other malignant pathologies encountered were ampullary carcinoma (2), hepatic metastases (2), pancreatic metastases (1), neuroendocrine tumour (1) and lymphoma (1). The specificity for malignancy was 100% and negative predictive value in diagnosing malignancy was 37.14%. Conclusion: Our sensitivity and positive predictive values of biliary brushings are the highest reported to date. This could be a result of rapid processing times of our specimens and availability of a histopathologist with interest in pancreatobiliary medicine. Presence of 'atypical cells' can be accepted as supporting the diagnosis of malignancy in the correct clinical context, as it will improve sensitivity. In view of its simplicity and effectiveness, we recommend biliary brushing during ERCP for all biliary strictures. Disclosure of interest: None Declared.